THEORIES AND SUCCESS STORIES OF ADVERTISING AND PUBLIC RELATIONS - Setia Budhi Wilardjo (Value Added : Majalah Ekonomi dan Bisnis, 2012)
Now that we are looked at overall integrated marketing communication planning, we dig more deeply into the specific marketing communications tools. In this article, we explore advertising and public relations. Advertising involves communicating the company’s or brand’s value proposition by using paid media to inform, persuade, and remind consumers. Public relations involves building good relations with various company publics – from consumers and the general public to the media, investor, donor, and government publics. As with all the promotion mix tools, advertising and public relations must be blended into the overall integrated marketing communications program. Keywords: integrating communication planning, advertising, public relations